Kajian Mekanisme Pemecahan Tanah Kavling Untuk Pengembangan Perumahan Di Kawasan BSD City - Herlin Sukmarini; Ririn Riandi (Magister Kajian Pembangunan Perkotaan dan Wilayah, 2024)
Land is a natural resource that does not increase and has a tendency for land prices to continue to increase due to hogh demand while land availability is limited. Currently, the availability of land for residences in the strategic housing area of BSD City is very difficult to reach because the prices are high, especially for the millennial generation because land prices are increasingly expensive and the plot size is 250 m2 above the average residential needs of the millennial generation. Everyone has the right to a prosperous life born and minded, a place to live, and a good and healthy living environment, according to the Preamble to the 1945 Constitution and Article 28 H paragraph 1 of the 1945 Constitution. In addition, Law Number 1 of 2011 concerning housing and organizations stipulates that everyone has the right to live a prosperous life both physically and mentally, to live, and to get a good and healthy living environment, which is a basic human need. By definition, plots of land are parts of land that have been plotted in certain sizes to be used as buildings or houses. According to the BigIndonesia Dictionary (KBBI), plots of land or plots are parts of land that have been plotted in certain sizes for buildings or redidences. The land certicates have also been broken down according to land parcels. This situation is the background for conducting a study on how to utilize unsold/abandoned plots of land as an effort to meet residential needs through a mechanism for spilitting plots of land for housing development.